Effects of Carotid plaque Crouse score and serum Hcy on the location of white matter hyperintensities - Liu, Yue; Tian, Xintao; Cheng, Xinrui; Jia, Chunyan; Li, Cuiping; Yang, Shaonan (Frontiers in Neurology, 2025)
Background and objectiveCarotid plaque Crouse score and serum homocysteine (Hcy) are closely associated with white matter hyperintensities (WMH). In recent years, it had been found that the pathological mechanism of periventricular WMH (PVWMH) and deep subcortical WMH (DSWMH) was different. In this study, we aimed to further determine the respective effects of Carotid plaque Crouse score and serum Hcy on the location of WMH.MethodsWe recruited 284 patients with lacunar infarction admitted to the Affiliated Hospital of Qingdao University and conducted a retrospective cohort study. The level of serum Hcy was determined by ELISA. Carotid plaque Crouse score was evaluated by cervical vascular ultrasound. The severity of PVWMH and DSWMH was graded using a manual rating scale. Logistic regression analysis was performed to explore the relationship between Crouse score, serum Hcy and PVWMH and/or DSWMH. The critical point which Crouse score and serum Hcy played a role was determined by Quartile method.ResultsAfter adjusting for confounding variables, Logistic regression showed that PVWMH was associated with age, hypertension, Hcy and Crouse score; DSWMH was associated with age, hypertension, and Crouse score but not with Hcy. Quartile analysis indicated that Crouse score > 0.39 was associated with the occurrence of PVWMH and DSWMH, while Hcy > 12.48 was only associated with the occurrence of PVWMH.ConclusionCrouse score is associated with both PVWMH and DSWMH. High levels of Hcy is associated with the occurrence of PVWMH, but not DSWMH.